Deep-water parasite diversity in Lake Tanganyika: description of two new monogenean species from benthopelagic cichlid fishes - Kmentová, Nikol; Gelnar, Milan; Koblmüller, Stephan; Vanhove, Maarten P M (Parasites & vectors, 2016)
BACKGROUND: Lake Tanganyika is the world's second deepest lake. Its diverse cichlid assemblage offers a unique opportunity for studying a deep-water host-parasite model in freshwater. Low host specificity and a broad host range including representatives of the Bathybatini tribe in the only monogenean parasite described from this habitat, Cichlidogyrus casuarinus Pariselle, Muterezi Bukinga & Vanhove, 2015 suggest a link between lower specificity and lower host density. Conversely, high host specificity and species richness are reported for monogeneans of the lake's littoral cichlids. We further investigated whether the deep-water environment in Lake Tanganyika is really monogenean species-depauperate by investigating the monogenean fauna of Trematocara unimaculatum (a representative of the tribe Trematocarini, the sister lineage of the Bathybatini) and Benthochromis horii, a member of the tribe Benthochromini, found in the same deep-water habitat as the already known hosts of C. casuarinus. METHODS: Sclerotised structures of the collected monogenean individuals were characterised morphologically using light microscopy and morphometrics. RESULTS: Both examined cichlid species are infected by a single monogenean species each, which are new to science. They are described as Cichlidogyrus brunnensis n. sp., infecting T. unimaculatum, and Cichlidogyrus attenboroughi n. sp., parasitising on B. horii. Diagnostic characteristics include the distal bifurcation of the accessory piece in C. brunnensis n. sp. and the combination of long auricles and no heel in C. attenboroughi n. sp. In addition C. brunnensis n. sp. does not resemble C. casuarinus, the only species of Cichlidogyrus thus far reported from the Bathybatini. Also Cichlidogyrus attenboroughi n. sp. does not resemble any of the monogenean species documented from the pelagic zone of the lake and is among the few described species of Cichlidogyrus without heel. CONCLUSIONS: As two new and non-resembling Cichlidogyrus species are described from T. unimaculatum and B. horii, colonisation of the deep-water habitat by more than one morphotype of Cichlidogyrus is evident. Based on morphological comparisons with previously described monogenean species, parasite transfers with the littoral zone are possible. Therefore, parasites of pelagic cichlids in the lake do not seem to only mirror host phylogeny and the evolutionary history of this host-parasite system merits further attention.
Keywords: Cichlidae; Gills; biodiverzita; žábry; Cichlidogyrus; Trematode Infections; jezera; Trematocara unimaculatum; Cichlids; cichlidy; zvířata; Tanzanie; Monogenea; Host Specificity; nemoci ryb; fylogeneze; Host-Parasite Interactions; Lakes; Trematoda; Biodiversity; interakce hostitele a parazita; Fish Diseases; Tanzania; Benthochromis horii; Phylogeny; hostitelská specificita; infekce červy třídy Trematoda; Animals